Evaluation of Immunomagnetic Separation-Polymerase Chain Reaction in Direct Detection of Brucella abortus and Brucella melitensis from Cheese Samples - Oengoer, H.; Cetinkaya, B.; Karahan, M.; Bulut, H. (Mary Ann Liebert, Inc, 2006)
The current study was carried out to assess the use of immunomagnetic separation-polymerase chain reaction (IMS-PCR) in direct detection of Brucella abortus and B. melitensis from soft cheese and to examine a relatively small number of field samples for the presence of these species. Two methodologies, one with IMS and the other without IMS, were employed for recovery of the Brucella species from cheese samples. IMS in conjunction with the PCR assay was determined to detect as low as 3 x 10(2) bacteria/mL, while the limit of detection with the other extraction procedure was 3 x 10(3) bacteria/mL. In the analysis of 40 cheese samples collected from various markets, only B. abortus was detected by PCR using both DNA extraction procedures in two (5%) samples. No positive results were obtained by culture and B. melitensis was not found in any cheese samples examined. The results suggest that this technique is promising owing to its pace and high sensitivity and should aid in direct detection of Brucella species from complex food samples.
Keywords: Escherichia-Coli O157; Raw-Milk; Sheep; Goats; Spp.; Pcr